PENGARUH KETERBUKAAN EKONOMI, NILAI TUKAR, PENANAMAN MODAL ASING DAN INFLASI TERHADAP CADANGAN DEVISA NEGARA INDONESIA - Fazrin Meinita Sukoco (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study aims to see the effect of economic openness, exchange rates, foreign investment, and inflation on foreign exchange reserves in Indonesia. This study uses the Autoregressive Distributed Lag (ARDL) model analysis using the Eviews 12 analysis tool. This study uses secondary data consisting of economic openness, exchange rates, foreign investment, inflation, and Indonesia's foreign exchange reserves for the period 1980 to 2021. In this study, the results show that the variable exchange rate and foreign investment have an effect on Indonesia's foreign exchange reserves. For the variable economic openness, it has a negative effect, namely reducing Indonesia's foreign exchange reserves and inflation has no effect on foreign exchange reserves.